Quantitative source identification and risk assessment of trace elements in soils from Leizhou Peninsula, South China. Issue 7 (3rd October 2019) - Gao, Lei; Wang, Zhuowei; Zhu, Aiping; Liang, Zuobing; Chen, Jianyao; Tang, Changyuan
ABSTRACT: Differentiating contribution of natural sources and anthropogenic inputs to soil element concentrations can provide important basis for pollution and risk assessments. Fifty-five surface soil samples were collected from farmland ( n = 33) and forest land ( n = 22) in the Leizhou Peninsula for the measurement of trace elements (Cr, Co, Ni, Cu, Zn, As, Pb, and Cd) concentrations. It was found that soil Cr, Ni, Cu, Zn and Cd concentrations were significantly higher in farmland soils than in forest soils ( p < 0.05). Industrial discharges accounted for the increase in Cr, Co, Ni, and Cu concentrations with mean contribution rates of 10.9%, 29.4%, 23.2%, and 25.3%, whereas agricultural activities contributed significantly (14.6%−92.4%) to soil Cd levels. The pollution levels of individual element based on a geo-accumulation index, and enrichment and contamination factors roughly followed a decreasing order of Cd > Co ≈ Cu ≈ Ni ≈ Cr > Zn ≈ As ≈ Pb. Severe contamination was found near industrial areas, which resulted in a moderate or considerable ecological risk. Soil Cr mainly derived from weathering process of basaltic rocks and industrial sources resulted in non-carcinogenic hazard and carcinogenic risk indices up to 2.47 and 2.79 × 10 –4, respectively, near industrial areas, leading to that children suffered more from higher non-carcinogenic and carcinogenic risks than adults.